Increased Caseload Volume is Associated With Better Oncologic Outcomes After Laparoscopic Resections for Colorectal Cancer. Issue 1 (February 2016) - Benlice, Cigdem; Baca, Bilgi; Firidin, Sadiye Nur; Muti, Aybuke; Aytac, Erman; Erguner, Ilknur; Erdamar, Sibel; Senocak, Mustafa; Turna, Hande; Hamzaoglu, Ismail; Karahasanoglu, Tayfun
Abstract : Purpose: To evaluate the impact of caseload volume on the outcomes of open and laparoscopic surgery for colorectal cancer. Methods: Between April 1999 and January 2011, patients who underwent open or laparoscopic resection for colorectal adenocarcinoma with curative intent were identified. There were 2 groups of surgeons, whose primary practice is gastrointestinal surgery (n=5, group A) and general surgery (n=14, group B). Histopathologic and oncologic outcomes, as well as survival data were evaluated. Results: A total of 815 patients fulfilled the study criteria and 356 (group A: 120, group B: 236) patients who had >2 years' follow-up data were included. Colorectal procedures constituted 33% and 19% of all the operations in A and B groups, respectively ( P <0.0001). Among the colorectal cases, rates of laparoscopic surgery were 37% and 20% in the group A and B, respectively ( P <0.0001). Practice pattern was independently associated with better overall survival and was favoring the group A ( P =0.02). Conclusions: Increased caseload volume improves oncologic outcomes in patients undergoing colorectal resection for nonmetastatic cancer.